British cinema of the 1950s A celebration - Sinyard, Neil (Manchester University Press, 2003)
This book offers a startling re-evaluation of what has until now been seen as the most critically lacklustre period of the British cinema. Twenty writers contribute essays that rediscover and reassess the productions of the Festival of Britain decade, during which the vitality of wartime film-making flowed into new forms. Topics covered include genres such as the B-film, the war film, the woman's picture, the theatrical adaptation and comedy; also social issues such as censorship and the screen representation of childhood. The book includes fresh assessments of maverick directors such as Pat Jackson, Robert Hamer and Joseph Losey, and even of a maverick critic, Raymond Durgnat. There are also three personal views from people individually implicated in 1950s cinema: Corin Redgrave on Michael Redgrave, Isabel Quigly on film reviewing, and Bryony Dixon of the British Film Institute on film archiving and preservation. In its evocation and coverage of a fascinating time when the national cinema enjoyed an unprecedented popularity amongst home audiences, this volume offers the most exhilarating survey yet of 1950s British film. In its provocative challenge to conventional wisdom about this decade's movies, the book will prove indispensable to students of the cinema at all levels and a stimulating companion for the critic and the historian.